Penerapan Elemen Budaya Korea Pada Perancangan Korean Cultural Center Indonesia di Jakarta Selatan - Nelwan, Meisya Mutiara; Wiyono, Erina (Fakultas Desain Universitas Komputer Indonesia, 2024)
South Korea is a country that is developing and progressing rapidly in all fields, including politics, economy, culture, and technology. Despite its rapid development, South Korea still maintains its cultural distinctiveness. This is a distinct advantage for the Korean state compared to other developed countries where most of the original culture has faded due to the development of the economy and technology. As a Cultural Center, it should have facilities such as facilities to introduce the culture of a country, but the interior atmosphere of KCCI still does not reflect Korean Culture and has not brought up Korean branding (Hallyu). Therefore, there is a need for a new design of the South Korean Cultural Center which has the aim of spreading Korean culture to increase the branding of the Korean state in accordance with the vision and mission of KOCIS by providing educational, informative, and recreational facilities to the people of Indonesia. The provision of Korean cultural elements is also very influential in this design including the provision of Korean calligraphy, Korean paintings, Mugunghwa flower motifs, and wood materials to give a more aesthetic impression of Korean culture itself.